Comorbidities significantly impact patients’ preferences for psoriasis treatments - Schmieder, Astrid; Schaarschmidt, Marthe-Lisa; Umar, Nasir; Terris, Darcey D.; Goebeler, Matthias; Goerdt, Sergij; Ludwig-Peitsch, Wiebke (Journal of the American Academy of Dermatology, 2012)
Background: Non-adherence rates are high among patients with psoriasis, partly because of discordance between recommended treatments and individual preferences. Objectives: Our aim was to assess the impact of comorbidities on patients’ preferences for psoriasis treatments. Methods: A computer-based conjoint analysis experiment was conducted to analyze preferences of patients with psoriasis (N = 163) for treatment outcome attributes (probability, magnitude and duration of benefit; probability, severity and reversibility of side effects) and process attributes (treatment location, frequency, duration, delivery method, individual cost). The impact of comorbidities (psoriatic arthritis, cardiovascular disease, diabetes, and depression) on relative importance scores of each attribute was assessed by analyses of variance, post hoc test, and multivariate regression analysis. Results: Among the participants included (58.9% males, mean age 49.3 yrs), 27% suffered from psoriatic arthritis, 13.5% from cardiovascular disease, 8% from diabetes, and 12.9% from depression. Preferences for treatment attributes varied significantly depending on comorbidities. Participants with psoriatic arthritis cared most about the probability of benefit (β 0.166; P = .037), whereas those participants with cardiovascular disease were highly concerned about the probability of side effects (β 0.179; P = .046). For participants with depression, treatment duration (β 0.163; P = .047), and individual cost (P = .023) were highly important. Limitations: Only patients with moderate and severe psoriasis treated at a university medical center were included. Conclusions: Integrating patients’ preferences into shared decision-making may facilitate treatment adherence and optimize outcomes. Addressing patients’ comorbidities, particularly depression, may be a currently neglected opportunity to improve care.
Available online 18 October 2011
Gesehen am 06.06.2018